2012
DOI: 10.3390/ph5091008
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 (Hsp90) Expression and Breast Cancer

Abstract: Hsp90 is an abundant protein in mammalian cells. It forms several discrete complexes, each containing distinct groups of co-chaperones that assist protein folding and refolding during stress, protein transport and degradation. It interacts with a variety of proteins that play key roles in breast neoplasia including estrogen receptors, tumor suppressor p53 protein, angiogenesis transcription factor HIF-1alpha, antiapoptotic kinase Akt, Raf-1 MAP kinase and a variety of receptor tyrosine kinases of the erbB fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…Therefore, these pathways have a key role in resistance to aromatase inhibitors and also act as HSP90 client proteins. 71 Wong et al 72 suggested that HSP90 inhibitors are effective against aromatase inhibitor-resistant breast cancers. HSP90 is associated with various miRNAs, and miRNA-based inhibition of HSP90 is easier to achieve than miRNA-based HSP70 inhibition.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…Therefore, these pathways have a key role in resistance to aromatase inhibitors and also act as HSP90 client proteins. 71 Wong et al 72 suggested that HSP90 inhibitors are effective against aromatase inhibitor-resistant breast cancers. HSP90 is associated with various miRNAs, and miRNA-based inhibition of HSP90 is easier to achieve than miRNA-based HSP70 inhibition.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…Consequently, many of the Hsp90 inhibitors previously mentioned have been examined at the clinical level as a novel chemotherapeutic intervention for HER2 positive breast carcinoma, with variable results being attained [78,44,79,80]. In the initial study of PU-H71, the agent demonstrated a very high propensity to initiate the degradation of HER2, and subsequently was notably cytotoxic against malignant, but not normal cells [21].…”
Section: Breast Carcinomamentioning
confidence: 99%
“…HSP90 is frequently overexpressed and activated in cancer cells, including acute leukemias [41], gastrointestinal cancers [42], glioblastoma [43], cervical cancer [44], lung cancers [45] and human breast cancers [46]. Several studies have shown that HSP90 is localized in the cytoplasm and on the cell surface in certain types of cancer cells [47], including prostate cancer [48], melanomas [49], non-small-cell lung cancer cells [50], fibrosarcoma cells [51], lymphomas [52] and breast cancer cell [53].…”
Section: Discussionmentioning
confidence: 99%